إشكالات التخطيط العمراني للمدن الجزائرية بين الواقع و المأمول. - Hassani, Ghada; Belimane, Yamina (Journal of Human Sciences, 2022)
The issue of urbanization in the Algerian city and improving the level of its performance is very difficult and complex as, it suffers from old difficulties inherited difficulties from the colonial era ,that have left deep-seated crises that are not easy if not Impossible to eradicate , and other new problems resulting from profound accumulation of complex urban policies that were adopted by Algeria after the independence characterized by many defects and lacks on the urban planning and the execution as well as the weakness of the control which worsen and complicates the situation .